Assessing the long‐term carbon‐sequestration potential of the semi‐natural salt marshes in the European Wadden Sea. Issue 1 (15th January 2019) - Mueller, Peter; Ladiges, Nils; Jack, Alexander; Schmiedl, Gerhard; Kutzbach, Lars; Jensen, Kai; Nolte, Stefanie
Abstract: Salt marshes and other blue carbon ecosystems have been increasingly recognized for their carbon (C)‐sink function. Yet, an improved assessment of organic carbon (OC) stocks and C‐sequestration rates is still required to include blue C in C‐crediting programs. Particularly, factors inducing variability in the permanence of sequestration and allochthonous contributions to soil OC stocks require an improved understanding. This study evaluates the potential for long‐term C sequestration in the semi‐natural salt marshes of the European Wadden Sea (WS), conducting deep (1.3 m) down‐core OC‐density assessments in sites with known site histories and accretion records. Because these young marshes have developed from tidal‐flat ecosystems and have undergone rapid succession during the last 80–120 yr, the identification of different ecosystem stages down‐core was crucial to interpret possible changes in OC density. This was conducted based on the down‐core distribution of different foraminiferal taxa and grain sizes. Comparisons of historic and recent accretion rates were conducted to understand possible effects of accretion rate on down‐core changes in OC density. δ 13 C in OC was used to assess the origin of accumulated OC (autochthonous vs. allochthonous sources). We show that large amounts of short‐term accumulated OC are lost down‐core in the well‐aerated marsh soils of the WS region and thus emphasize the importance of deep sampling to avoid overestimation of C sequestration. Despite steep declines in OC‐density down‐core, minimum values of OC density in the salt‐marsh soils were considerably higher than those of the former tidal‐flat sediments that the marshes were converted from, illustrating the greater C‐sequestration potential of the vegetated ecosystem. However, our data also suggest that marine‐derived allochthonous OC makes up a large fraction of the effectively, long‐term preserved OC stock, whereas atmospheric CO2 removal by marsh vegetation contributes relatively little. The implication of this finding for C‐crediting approaches in blue C ecosystems has yet to be clarified.